Consumer Communication and Organisational Strategies for Animal Welfare by the Food and Retail Industries in Italy. (7th August 2013) - Mancini, Maria Cecilia; Arfini, Filippo
Summary: Consumer Communication and Organisational Strategies for Animal Welfare by the Food and Retail Industries in Italy: The treatment of animals used in production processes involves ethical principles as well as food safety and has become increasingly a focus of debate. Based on survey evidence, this article examines consumer communication and organisational strategies regarding animal welfare (AW) by food processors and retailers in Italy. It identifies three levels of commitment to animal welfare: full sensitivity with regard to ethical issues and products; animal welfare seen solely as an aspect of product quality; and indifference where animal welfare is considered purely a legal obligation. This classification could be a starting point for institutional intervention. 'Active' behaviour shows that AW can be used as a means of organisational renewal of supply chain mechanisms and thus could be supported by public institutions. At the same time, an effective implementation of EU AW policy requires public intervention to ensure that consumers receive the information they need to shop with awareness of AW issues. It is only through greater awareness of AW friendly techniques and their implications that willingness to pay among Italian consumers will increase. This in turn will provide the incentives for producers, processors and retailers to show more interest in AW‐friendly techniques. Abstract : The treatment of animals used in production processes involves ethical principles as well as food safety and has become increasingly a focus of debate.